2021
DOI: 10.3389/fcvm.2021.713983
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of Atrial-Fibrillation-Related Innate Immunity Gene ANXA4

Abstract: Background: Atrial fibrillation (AF) is the most common tachyarrhythmia around the world. Cancer is one of the main causes of death worldwide. A recent study demonstrated that cancer was associated with an increased incidence of AF. In the present study, we aimed to explore possible mechanisms and potential common therapeutic targets between AF and cancer.Methods: Differentially expressed proteins between AF and sinus rhythm were identified utilizing proteomics analysis. Weighted gene correlation network analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Recent studies have identified ANXA4 gene as a hub immune‐related gene in AF, with significantly higher levels of ANXA4 expression in patients with AF than in normal subjects. 53 This may be related to the fact that ANXA4 affects the cardiac action potential or influences the contractility of the left atrium. 54 , 55 RAB1A is a member of the Ras superfamily of guanosine triphosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified ANXA4 gene as a hub immune‐related gene in AF, with significantly higher levels of ANXA4 expression in patients with AF than in normal subjects. 53 This may be related to the fact that ANXA4 affects the cardiac action potential or influences the contractility of the left atrium. 54 , 55 RAB1A is a member of the Ras superfamily of guanosine triphosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…TIMPs could control MMP that could lead to the degradation of the extracellular matrix and, consequently, organize the path for malignant cells to progress and spread to distant secondary areas ( 47 ). Third, certain immune-related genes identified in AF have recently been linked to the prognosis and immune infiltration in several tumor types ( 48 ). Herein, present KEGG and GO enrichment analyses of 51 common DEGs also revealed that these genes were significantly enriched in antioxidant activity, xenobiotic catabolic processes, and cytochrome P450 metabolism pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that ANXA4 could play a role in modulating immune cell function and potentially impact tumor immune response. [ 31 ] VSIG4 encodes a transmembrane protein that regulates macrophage function. Recent research indicates that VSIG4 might be involved in modulating tumor immune response by regulating immune cell activity.…”
Section: Discussionmentioning
confidence: 99%